Factors associated with severe or fatal clinical manifestations of SARS‐CoV‐2 infection after receiving the third dose of vaccine. (9th August 2022) - Corrao, Giovanni; Franchi, Matteo; Cereda, Danilo; Bortolan, Francesco; Leoni, Olivia; Jara, Jose; Valenti, Giuseppina; Pavesi, Giovanni
Abstract: Background: Little is known about vulnerability to severe COVID‐19 illness after vaccination completion with three doses of vaccine against COVID‐19. Objectives: To identify individual features associated with increased risk of severe clinical manifestation of SARS‐CoV‐2 infections after receiving the third dose of vaccine against COVID‐19. Methods: We performed a nested case‐control study based on 3, 360, 116 citizens from Lombardy, Italy, aged 12 years or older who received the third dose of vaccine against COVID‐19 from 20 September through 31 December 2021. Individuals were followed from 14 days after vaccination completion until the occurrence of severe COVID‐19 illness, death unrelated to COVID‐19, emigration or 15 March 2022. For each case, controls were randomly selected to be 1:10 matched for the date of vaccination completion and municipality of residence. The association between candidate predictors and outcome was assessed through multivariable conditional logistic regression models. Results: During 12, 538, 330 person‐months of follow‐up, 5171 cases of severe illness occurred. As age increased, a trend towards increasing odds of severe illness was observed. Male gender was a significant risk factor. As the number of contacts with the Regional Health Service increased, a trend towards increasing odds of severe illness was observed. Having had a previous SARS‐CoV‐2 infection was a significant protective factor. Having received the Moderna vaccine significantly decreased the odds of severe illness. Significant higher odds were associated with 42 diseases/conditions. Odds ratios ranged from 1.23 (diseases of the musculoskeletal system) to 5.00 (autoimmune disease). Conclusions: This study provides useful insights for establishing priority in fourth‐dose vaccination programs. Abstract : .